2002
DOI: 10.1023/a:1020859405262
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this work was to investigate the relationship between mechanisms of DNA repair and apoptosis induced by oxidative stress (H2O2) in human lymphocytes. Using the comet assay, fluorescent microscopy, and DNA electrophoresis, we studied the DNA damage induced by hydrogen peroxide (H2O2) treatment, the time and the amount of repair of strand breaks, the type of cell death, and the influence of inhibitors of repair (nicotinamide). When lymphocytes were treated with H2O2, we observed an increased in necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…PARP-1 inhibition by nicotinamide has been shown to switch the mode of cell death from necrosis to apoptosis in ex vivo human lymphocytes treated with hydrogen peroxide [124]. In addition, it has been widely reported that in the cells exposed to oxidative stress, both ATP and NAD + levels serve as crucial molecular switches between apoptosis and necrosis [125133].…”
Section: Nicotinamide Parp-1 and Cellular Responses To Dna Damagementioning
confidence: 99%
“…PARP-1 inhibition by nicotinamide has been shown to switch the mode of cell death from necrosis to apoptosis in ex vivo human lymphocytes treated with hydrogen peroxide [124]. In addition, it has been widely reported that in the cells exposed to oxidative stress, both ATP and NAD + levels serve as crucial molecular switches between apoptosis and necrosis [125133].…”
Section: Nicotinamide Parp-1 and Cellular Responses To Dna Damagementioning
confidence: 99%
“…One of the ROS which causes DNA damage is H 2 O 2 . H 2 O 2 induces double strand breaks (DSBs), which are followed by DNA repair [1], [2]. The H 2 O 2 -induced DNA repair measured in peripheral blood mononuclear cells (PBMC) has been previously used in our laboratory [1], [3], [4].…”
Section: Introductionmentioning
confidence: 99%